Hubungan Dukungan Keluarga dengan Kepatuhan Minum Obat pada Pasien Skizofrenia - Siagian, Ira Ocktavia; Siboro, Elva N P; Julyanti (Jurnal Kesehatan, 2022)
Family support is a very important factor in the healing process of schizophrenia patients by supporting medication adherence so that the patient's recovery period can be maintained as long as possible. This study aims to determine the relationship between family support and medication adherence in schizophrenic patients at the Sangkanhurip Health Center. This research is a quantitative study with an analytic survey design and cross-sectional approach. The research sample were 39 schizophrenic patients that were recruited using a total sampling approach. The instruments used in this study were the medication adherence instrument, namely the Morisky Medication Adherence Scale (MMAS-8) and the family support instrument. The reliability of the family support questionnaire was 0.759 and medication adherence was 0.762. The data obtained from this study was analyzed using bivariate analysis, namely Chi-Square test. The research results showed that most of the respondents (59%) have low family support and most of the respondents (51.3%) have low medication adherence. There is a significant relationship between family support and medication adherence in schizophrenic patients at the Sangkanhurip Health Center (p-value=0.000). It is hoped that the family will gain knowledge about the benefits of being obedient in taking medication, particularly from health education using health education media from health professionals, so that it can reduce the occurrence of complications.